Stakeholder analysis of climate projects implemented within green areas - Kolarzh Vyacheslav; Karamyshev Viktor (BIO Web of Conferences)
Natural climate projects are a promising tool for achieving carbon neutrality of the Russian economy. However, at the moment, green areas, the creation of which may be mandatory, are actually excluded from the context of climate projects. This article presents the results of a stakeholder analysis for climate projects implemented in green areas. The results of the analysis can be used as basic prerequisites for developing algorithms for implementing climate projects in these areas.